Исследование кинетики селективной очистки от оксидов азота - Савенков, Анатолий Сергеевич; Яковишин, В. А.; Шапка, А. В.; Сибирцева, М. А.; Жигайло, Б. Д. (НТУ "ХПИ", 2005)
The process of selective reduction of nitrogen oxides on alumina-vanadia catalyst AVK – 10M is investigated in wide range of varying of parameters such as contact time, temperature, NH₃ to NOₓ ratio. The kinetic model accounting all technology parameters influence is created.
Keywords: восстановление селективное; катализатор алюмованадиевый; параметры технологические; кислота азотная